The Impact of Digital Competencies and Work Environment on Work Productivity: The Mediating Role of Work Effectiveness - Putri, Rizka Ardlia; Ismail, Gurawan Dayona; Mubarok, Dadan Abdul Aziz; Yoyo Sudaryo, Erna Herlinawati, (STIE AMKOP, 2024)
This paper explores the impact of digital competence and work environment on work productivity, focusing on how work effectiveness mediates these relationships. In the context of increasing digital transformation, understanding these dynamics is crucial for enhancing organizational performance and employee satisfaction. The study investigates how individual and combined factors of digital competence and work environment influence productivity, with a specific focus on the role of work effectiveness. The research uses a quantitative approach, collecting primary data through questionnaires from 78 frontliner employees at Bank Mandiri Asia Afrika Bandung. Statistical methods, including correlation testing, determination analysis, and hypothesis testing via t-tests and F-tests, were employed to analyze the relationships among the variables. Findings reveal that both digital competence and work environment positively affect work productivity, with work effectiveness significantly mediating these effects. The study concludes that enhancing digital skills and improving the work environment can substantially boost productivity by increasing work effectiveness. Organizations should invest in digital training and create supportive work conditions to maximize employee productivity through improved effectiveness. This comprehensive approach highlights the importance of integrating these factors to achieve optimal workplace performance. Keywords: Digital Competences, Work Environment, Work Effectiveness, Work Productivity, Banking